Flemingia macrophylla in goat feeding - Oiticica, Isabel das Neves; Moreira da Fonseca, Carlos Elysio; Souza, Vinicius Carneiro de [UNESP]; Silva, Aline Barros da; Ferraz Lopes, Fernando Cesar; Frota Morenz, Mirton Jose (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2015)
The objective of this work was to evaluate the inclusion of Fabaceae Flemingia macrophylla (Willd.) Kuntze ex Merr. in the diet of lactating dairy goats arranged in a 5 x 5 Latin square. The diets were composed of 40% of concentrate and 60% of roughage, and the dietary treatments were defined by the level of Flemingia hay inclusion (0%, 8%, 16%, 24%, and 32% in the diet dry matter) replacing Cynodon dactylon cv. Tifton 85 hay. The diets were isonitrogenous, with 14% crude protein. Feed intake, nutrient digestibility, feeding behavior, and ruminal pH and ammonia nitrogen were evaluated. There was no difference in dry matter intake with the inclusion of Flemingia hay in the diet. The digestibility of dry matter, organic matter, crude protein, neutral detergent fiber, and total carbohydrates decreased with the inclusion of Flemingia in the diet. The diet did not change rumen ammonia nitrogen concentration or ruminal pH. There were no differences in the feeding behavior or feed and rumination efficiencies. Flemingia macrophylla can be used up to the level of 32% in the dry matter in diets for lactating goats.
Keywords: digestibility; feeding behavior; leguminosae; ruminal pH; tropical forage